Nanocellulose / sodium acrylate / zwitterionic sulfobetaine composite gel electrolyte ink for 3D printing and preparation method and application of nanocellulose / sodium acrylate / zwitterionic sulfobetaine composite gel electrolyte ink
By modifying nanocellulose with sodium acrylate and zwitterionic sulfonate, the composite gel electrolyte ink is solved, and the existing 3D printing ink is harmful to the environment and poor conductivity is achieved, and a high-performance and environmentally friendly 3D printing molding material is achieved.
Patent Information
- Application Number
- CN202411880476.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The matrix materials of existing 3D printing reinforced composite ink are mostly derived from petroleum, which has slow natural degradation speed, is harmful to the environment, and has poor electrical conductivity, which limits the application of 3D printing technology in electronic device molding.
A composite gel electrolyte ink was prepared by forming a block polymer with sodium acrylate and zwitterionic sulfonate betaine. The ink is completely crosslinked by light induced under 365nm ultraviolet light to achieve rapid molding.
The ink has good biocompatibility, mechanical properties, environmental friendliness and mild molding conditions. It can be used for rapid 3D printing and molding of 3D polymer composite reinforcement materials, and has excellent comprehensive performance in electronic devices and other fields.
Smart Images

Figure CN119798543A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of 3D printing gel ink, and specifically relates to a 3D printing nanocellulose / sodium acrylate / zwitterion sulfonate betaine composite gel electrolyte ink and a preparation method and application thereof. Background Art
[0002] 3D printing is a technology that uses slices to reconstruct and restore trajectories to print three-dimensional objects. Due to its unique advantages in high-precision manufacturing, personalized customization, and complex shape construction, it is used in various industries. In recent years, 3D printing technology has been applied to the field of polymer composite materials to enhance the various properties of composite materials, such as mechanical properties and ion transmission properties.
[0003] Photocuring 3D printing uses ultraviolet light sources to control the layer-by-layer printing of 2D cross-sections of materials, and multi-layer polymerization to construct 3D electrodes. At present, the base materials of common 3D printing reinforced composite inks are photosensitive resins such as water-based polyurethane. These materials are mostly derived from petroleum, have a slow natural degradation rate, and large-scale use is harmful to the environment. In addition, these materials have poor conductivity, which greatly limits the application scope of 3D printing technology in the molding of electronic devices. Therefore, with the in-depth development of 3D printing molding technology in the field of reinforced composite materials, it is urgent to prepare a new type of environmentally friendly composite 3D printing ink that has both mechanical and electrochemical properties. Summary of the invention
[0004] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonated betaine composite gel electrolyte ink. Using modified nanocellulose as the polymer matrix of the 3D printing ink, the ink has good biocompatibility, mechanical properties, environmental friendliness and mild molding conditions, and can be used for rapid 3D printing of 3D polymer composite reinforced materials.
[0005] Another object of the present invention is to provide a method for preparing a 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink.
[0006] Another object of the present invention is to provide an application of the above-mentioned 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink is prepared from 20 to 40 parts by mass of sodium acrylate, 10 to 30 parts by mass of zwitterionic sulfonate betaine, 150 to 200 parts by mass of modified nanocellulose dispersion, 1 to 2 parts by mass of photoinitiator and 1 to 2 parts by mass of chemical crosslinking agent; the solid content of the modified nanocellulose dispersion is 4wt% to 6wt%; the modified nanocellulose is Tempo oxidized nanocellulose modified by 4-cyano-4-[[(dodecylthio)thionemethyl]thio]pentanoic acid.
[0009] The ink is a composite gel aqueous solution with modified nanocellulose as the skeleton and sodium acrylate and zwitterionic sulfonated betaine as block polymers; it is partially cross-linked when prepared; when used, the ink is irradiated with 365nm ultraviolet light to completely cross-link through light induction, so that it can be quickly formed and 3D printed.
[0010] Preferably, the zwitterionic sulfonate betaine is at least one of dodecyldimethylsulfopropyl betaine, octadecylethoxysulfobetaine, dodecylethoxysulfobetaine, and hexadecylhydroxypropylsulfobetaine; the chemical crosslinker is N,N-methylenebisacrylamide; and the photoinitiator is at least one of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 1-hydroxycyclohexylphenyl ketone, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
[0011] Preferably, the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink is prepared from 30 parts by mass of sodium acrylate, 20 parts by mass of zwitterionic sulfonate betaine, 150-200 parts by mass of modified nanocellulose dispersion, 1-2 parts by mass of photoinitiator and 1-2 parts by mass of chemical crosslinking agent.
[0012] More preferably, the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink is prepared from 30 parts by mass of sodium acrylate, 20 parts by mass of zwitterionic sulfonate betaine, 200 parts by mass of modified nanocellulose dispersion, 1 to 2 parts by mass of photoinitiator and 1 to 2 parts by mass of chemical crosslinking agent.
[0013] A method for preparing the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfobetaine composite gel electrolyte ink comprises the following steps:
[0014] (1) Preparing a Tempo-oxidized nanocellulose dispersion;
[0015] (2) mixing N,N-carbonyldiimidazole and 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid, heating and stirring to obtain activated acidic imidazole lactone; adding 1 to 5 parts by weight of activated acidic imidazole lactone to 90 to 150 parts by weight of the Tempo oxidized nanocellulose dispersion obtained in step (1) under an inert gas atmosphere, reacting under heating and stirring conditions, and dialyzing in water after the reaction is completed to obtain a Tempo oxidized nanocellulose dispersion grafted with 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid;
[0016] (3) Add 20 to 40 parts by mass of sodium acrylate and 10 to 30 parts by mass of zwitterionic sulfonic acid betaine to 150 to 200 parts by mass of the Tempo oxidized nanocellulose dispersion grafted with 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid obtained in step (2), add a chemical crosslinking agent and a photoinitiator under stirring, keep stirring to react, centrifuge to remove bubbles in the mixed dispersion after the reaction is completed, and let it stand to obtain the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonic acid betaine composite gel electrolyte ink.
[0017] Preferably, the specific steps of step (1) are: dispersing absolutely dry cellulose in water, adding Tempo (2,2,6,6-tetramethylpiperidinyl oxide), sodium bromide and sodium hypochlorite in sequence, stirring at room temperature, adding sodium hydroxide solution dropwise to keep the pH of the suspension at 9-11, and adding ethanol to terminate the reaction; then using a homogenizer to perform high-pressure homogenization on the washed oxidized cellulose to obtain a uniformly dispersed Tempo oxidized nanocellulose dispersion.
[0018] More preferably, in the high pressure homogenization, the homogenization pressure is 10 to 30 MPa and the number of homogenization times is 20 to 50 times.
[0019] Preferably, the solid content of the Tempo oxidized nanocellulose dispersion in step (1) is 2 wt% to 5 wt%.
[0020] Preferably, the solid content of the Tempo-oxidized nanocellulose dispersion grafted with 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid in step (2) is 4 wt % to 6 wt %.
[0021] Preferably, the molar ratio of N,N-carbonyldiimidazole to 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid in step (2) is 0.5-2.
[0022] Preferably, the reaction in step (2) is carried out at 30°C to 40°C with stirring for 3h to 6h, and the stirring speed is 500r / min to 1500r / min.
[0023] Preferably, the reaction in step (3) is carried out at 50°C to 80°C with stirring for 24h to 48h, and the stirring speed is 500r / min to 1500r / min.
[0024] The 3D printing nanocellulose / sodium acrylate / zwitterionic sulfobetaine composite gel ink prepared by the present invention is stored in the dark at room temperature, and has an effective shelf life of 6 months; when used, it is completely cross-linked by inducing ultraviolet light to achieve 3D printing molding;
[0025] The stirring conditions are: mechanical stirring for 10 min to 30 min at room temperature, and the mechanical stirring speed is 600 r / min to 1000 r / min;
[0026] The UV irradiation 3D printing processing gel conditions are: the bottom layer illumination time is 25 to 35 seconds, the illumination time of each layer is 20 seconds, the gel disc modeling thickness is 0.5 mm, and the number of slice layers is 20.
[0027] The gel can be processed in a controllable manner by adjusting the length of photopolymerization time. The gel exhibits good mechanical properties and high ionic conductivity in a thin film state. It can be used in supercapacitors, flexible wearable devices, and lightweight electronic devices, and provides more possibilities for 3D printed energy storage devices.
[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0029] 1. The 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonated betaine composite gel electrolyte ink provided by the present invention makes the nanocellulose macromolecules the center of the polymer polymerization reaction through modification, making the free radical reaction more gentle and controllable, overcoming the shortcomings of the prior art and simultaneously improving the formula and preparation process. The cellulose is used as the polymer matrix of the 3D printing ink, so that the ink has good biocompatibility, mechanical properties, environmental friendliness and mild molding conditions, and can be used for rapid 3D printing molding of 3D polymer composite reinforced materials.
[0030] 2. The 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink provided by the present invention has an efficient preparation method and a uniquely designed formula. The reaction principle is the free radical polymerization of sodium acrylate and zwitterionic sulfonate betaine initiated by light, and the layer-by-layer photopolymerization 3D printing composite polymer material for ultraviolet light rapid prototyping is used, wherein the addition amount of sodium acrylate and zwitterionic sulfonate betaine accounts for 11 to 38 wt% of the entire raw material system, and rapid crosslinking and molding can be achieved under ultraviolet light triggering.
[0031] 3. The 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonated betaine composite gel electrolyte ink provided by the present invention uses modified Tempo oxidized cellulose as the skeleton of the 3D printing ink, which provides free radical reaction centers for the photopolymerization reaction of the two polymers and also provides good mechanical properties for the molded material. The polymer matrix has a wide range of sources, low raw material costs, good biocompatibility and environmental friendliness, and can be used for the printing and preparation of polymer-reinforced composite materials in flexible electronic devices and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a scanning electron microscope image of the 3D printed nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink of Example 1 of the present invention;
[0033] Figure 2 is the ionic conductivity of the 3D printed nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink of Example 1 of the present invention;
[0034] Figure 3 is the ion migration number of the 3D printed nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink of Example 1 of the present invention;
[0035] Figure 4 is the ion migration number of the 3D printed nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink of Example 2 of the present invention;
[0036] Figure 5 This is a scanning electron microscope image of the 3D printed nanocellulose / sodium acrylate / zwitterionic sulfonated betaine composite gel electrolyte ink of Example 2 of the present invention;
[0037] Figure 6 It is a tensile stress-strain diagram of the 3D printed nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink of Examples 1 and 3 of the present invention.
[0038] Figure 7 It is the ion migration number of the 3D printed nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink of Example 3 of the present invention. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The raw materials involved in the present invention can be purchased directly from the market. For process parameters not particularly noted, conventional techniques can be used.
[0040] The performance test method of the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink prepared in the embodiment is as follows:
[0041] (1) The mechanical properties of the hydrogel were tested using a material testing machine (INSTRON 3300). Tensile test: A dumbbell-shaped sample was prepared using a rod-shaped mold. The hydrogel was axially stretched until the gel broke using a testing machine at a stretching speed of 20 mm / min. -1 There are 3 specimens in each group, and the mechanical properties are taken as the average value.
[0042] (2) Ionic conductivity. The battery was assembled in the order of stainless steel sheet, gel electrolyte, and stainless steel sheet. An electrochemical workstation (CHI 660E) was used to perform EIS test, and the ionic conductivity was calculated using Formula 1:
[0043]
[0044] Where L is the gel thickness, R is the resistance, and S is the contact area.
[0045] (3) Ion migration number. A Zn||Zn symmetric cell was assembled and tested using an electrochemical workstation (Admiral SquidstatPlus) using the chronoamperometry method (polarization voltage was 10 mV). An EIS test was performed before and after polarization. The migration number was finally calculated according to the formula (Formula 2):
[0046]
[0047] Wherein, I0 / Is and R0 / RS represent the initial / final current and resistance before and after the polarization test, respectively, and ΔV=10 mV.
[0048] Embodiment 1:
[0049] The preparation method of the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonated betaine composite gel electrolyte ink provided in this embodiment comprises the following steps:
[0050] (1) Disperse 1g of absolute dry cellulose in 100mL of water, add 0.016g of Tempo and 0.1g of sodium bromide in sequence, slowly add 6.5mL of liquid sodium hypochlorite, stir at room temperature, add 0.5mol / L of sodium hydroxide solution dropwise to keep the pH of the suspension at about 10 until it no longer changes, and add 10mL of ethanol to terminate the reaction. Then wash with a dialysis bag, and use a homogenizer to high-pressure homogenize the washed oxidized cellulose to obtain a uniformly dispersed Tempo oxidized nanocellulose dispersion; the homogenization pressure is 10Mpa, and the number of homogenizations is 20 times.
[0051] (2) N,N-Carbonyldiimidazole (CDI, 0.6 g, 3 mmol) and 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid (CDTPA, 0.8 g, 2.0 mmol) were dissolved in anhydrous DMSO (20 mL) and stirred at 40°C for 6 h to obtain activated acidic imidazole lactone. Subsequently, under an inert gas atmosphere, 1 g of the acidic imidazole lactone reaction mixture was added to 100 g of a 3% Tempo oxidized nanocellulose dispersion, and mechanically stirred at 30°C for 3 h at a mechanical stirring speed of 800 r / min. Finally, the crude product was dialyzed in water to obtain a 5% Tempo oxidized nanocellulose dispersion grafted with 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid.
[0052] (3) At room temperature, 3 g of sodium acrylate and 2 g of dodecyldimethyl sulfopropyl betaine were added to 20 g of the Tempo oxidized nanocellulose dispersion grafted with 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid obtained in step (2), followed by 100 mg of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide and 100 mg of N,N-methylenebisacrylamide, and the mixture was stirred evenly on a magnetic stirrer. The mixture was stirred mechanically for 36 h at a temperature of 60° C. and a mechanical stirring speed of 800 r / min; a uniform and transparent suspension was formed to obtain the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfobetaine composite gel electrolyte ink.
[0053] (4) The ink is poured into a DLP UV-curing 3D printing device, and after printing, mechanical properties, ionic conductivity, ion migration number and other performance tests are performed. The wavelength of the UV light is 365 nm, and the conditions for UV irradiation 3D printing of the gel electrolyte disc are: the bottom layer illumination time is 25 to 35 seconds, the illumination time of each layer is 20 seconds, the gel disc modeling thickness is 0.5 mm, and the number of slice layers is 20.
[0054] Figures 1 to 3 They are the scanning electron microscope image of the 3D printed nanocellulose / sodium acrylate / zwitterionic betaine sulfonate composite gel electrolyte ink prepared in this embodiment, the ion conductivity test results, and the ion migration number test results. The tensile stress-strain diagram is shown in Figure 6 As shown in the attached drawing, it can be seen that the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonated betaine composite gel electrolyte ink prepared in this embodiment has excellent comprehensive performance. In addition, after actual testing, the 3D printing ink prepared in this embodiment can be formed after 10 seconds of illumination.
[0055] Embodiment 2:
[0056] The preparation method of the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonated betaine composite gel electrolyte ink provided in this embodiment comprises the following steps:
[0057] (1) Disperse 1g of absolute dry cellulose in 100mL of water, add 0.016g of Tempo and 0.1g of sodium bromide in sequence, slowly add 6.5mL of liquid sodium hypochlorite, stir at room temperature, drop 0.5mol / L of sodium hydroxide solution to keep the pH of the suspension at about 10 until it no longer changes, and add 10mL of ethanol to terminate the reaction. Then wash with a dialysis bag, and use a homogenizer to high-pressure homogenize the washed oxidized cellulose to obtain a uniformly dispersed Tempo oxidized nanocellulose dispersion; the homogenization pressure is 10Mpa, and the number of homogenizations is 20 times.
[0058] (2) N,N-Carbonyldiimidazole (CDI, 0.6 g, 3 mmol) and 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid (CDTPA, 0.8 g, 2.0 mmol) were dissolved in anhydrous DMSO (20 mL) and stirred at 40°C for 6 h to obtain activated acidic imidazole lactone. Subsequently, under an inert gas atmosphere, 1 g of the acidic imidazole lactone reaction mixture was added to 100 g of a 3% Tempo oxidized nanocellulose dispersion and mechanically stirred at 30°C for 3 h at a mechanical stirring speed of 800 r / min. Finally, the crude product was dialyzed in water to obtain 5% Tempo oxidized nanocellulose grafted with 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid.
[0059] (3) At room temperature, 8 g of sodium acrylate, 8 g of dodecyldimethyl sulfopropyl betaine, and then 100 mg of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide and 100 mg of N,N-methylenebisacrylamide were added to 20 g of the Tempo oxidized nanocellulose dispersion grafted with 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid obtained in step (2) and stirred evenly on a magnetic stirrer. Mechanical stirring was performed at a temperature of 60° C. for 36 h at a mechanical stirring speed of 800 r / min to form a uniform and transparent suspension, thereby obtaining the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfobetaine composite gel electrolyte ink.
[0060] (4) The ink is poured into a DLP UV-curing 3D printing device, and after printing, the performance tests such as ion conductivity and ion migration number are performed. The wavelength of the UV light is 365 nm, and the conditions for UV irradiation 3D printing of the gel electrolyte disc are: the bottom layer irradiation time is 25 to 35 seconds, the irradiation time of each layer is 20 seconds, the modeling thickness of the gel disc is 0.5 mm, and the number of slice layers is 20.
[0061] Figures 4-5 The 3D printed nanocellulose / sodium acrylate / zwitterionic sulfonated betaine composite gel electrolyte ink prepared in this embodiment has ionic conductivity and ion migration number test results, respectively. It can be seen from the figure that the electrochemical performance of the gel is poor. In addition, the 3D printed nanocellulose / sodium acrylate / zwitterionic sulfonated betaine composite gel electrolyte ink prepared in this embodiment can be printed by adjusting the printing parameters of 3D printing and printed under the condition of 10S illumination time per layer, but due to the high concentration of the polymerized monomer, the gel chain is densely polymerized.
[0062] Embodiment 3:
[0063] The preparation method of the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonated betaine composite gel electrolyte ink provided in this embodiment comprises the following steps:
[0064] (1) Disperse 1g of absolute dry cellulose in 100mL of water, add 0.016g of Tempo and 0.1g of sodium bromide in sequence, slowly add 6.5mL of liquid sodium hypochlorite, stir at room temperature, drop 0.5mol / L of sodium hydroxide solution to keep the pH of the suspension at about 10 until it no longer changes, and add 10mL of ethanol to terminate the reaction. Then wash with a dialysis bag, and use a homogenizer to high-pressure homogenize the washed oxidized cellulose to obtain a uniformly dispersed Tempo oxidized nanocellulose dispersion; the homogenization pressure is 10Mpa, and the number of homogenizations is 20 times.
[0065] (2) N,N-Carbonyldiimidazole (CDI, 0.6 g, 3 mmol) and 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid (CDTPA, 0.8 g, 2.0 mmol) were dissolved in anhydrous DMSO (20 mL) and stirred at 40°C for 6 h to obtain activated acidic imidazole lactone. Subsequently, under an inert gas atmosphere, 1 g of the acidic imidazole lactone reaction mixture was added to 100 g of a 3% Tempo oxidized nanocellulose dispersion and mechanically stirred at 30°C for 3 h at a mechanical stirring speed of 800 r / min. Finally, the crude product was dialyzed in water to obtain 5% Tempo oxidized nanocellulose grafted with 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid.
[0066] (3) At room temperature, 3 g of sodium acrylate, 2 g of dodecylethoxysulfobetaine, and then 100 mg of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide and 100 mg of N,N-methylenebisacrylamide were added to 20 g of the Tempo oxidized nanocellulose dispersion grafted with 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid obtained in step (2) and uniformly stirred on a magnetic stirrer. Mechanical stirring was performed at a temperature of 60° C. for 36 h at a mechanical stirring speed of 800 r / min to form a uniform and transparent suspension, thereby obtaining the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfobetaine composite gel electrolyte ink.
[0067] (4) The ink is poured into a DLP UV-curing 3D printing device, and after printing, mechanical properties, ion migration number and other performance tests are performed. The wavelength of the UV light is 365 nm, and the conditions for UV irradiation 3D printing of the gel electrolyte disc are: the bottom layer illumination time is 25 to 35 seconds, the illumination time of each layer is 20 seconds, the gel disc modeling thickness is 0.5 mm, and the number of slice layers is 20.
[0068] Figures 6-7 They are respectively the tensile stress-strain and ion migration number test results of the 3D printed nanocellulose / sodium acrylate / zwitterionic sulfonated betaine composite gel electrolyte prepared in this embodiment. From the test results of the attached figure, it can be seen that the 3D printed nanocellulose / sodium acrylate / zwitterionic sulfonated betaine composite gel electrolyte ink prepared in this embodiment has excellent comprehensive performance. In addition, after actual testing, the 3D printed ink prepared in this embodiment can be formed after 10S of illumination time.
[0069] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink, characterized in that: The invention is prepared from 20 to 40 parts by weight of sodium acrylate, 10 to 30 parts by weight of zwitterionic sulfonated betaine, 150 to 200 parts by weight of modified nanocellulose dispersion, 1 to 2 parts by weight of photoinitiator and 1 to 2 parts by weight of chemical crosslinking agent; the solid content of the modified nanocellulose dispersion is 4wt% to 6wt%; the modified nanocellulose is Tempo oxidized nanocellulose modified by 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid.
2. A 3D printing nanocellulose / sodium acrylate / zwitterionic sulfobetaine composite gel electrolyte ink according to claim 1, characterized in that: The 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink is prepared from 30 parts by mass of sodium acrylate, 20 parts by mass of zwitterionic sulfonate betaine, 150-200 parts by mass of modified nanocellulose dispersion, 1-2 parts by mass of photoinitiator and 1-2 parts by mass of chemical crosslinking agent.
3. A 3D printing nanocellulose / sodium acrylate / zwitterionic sulfobetaine composite gel electrolyte ink according to claim 1 or 2, characterized in that: The zwitterionic sulfonate betaine is at least one of dodecyldimethylsulfopropyl betaine, octadecylethoxysulfo betaine, dodecylethoxysulfo betaine, and hexadecylhydroxypropylsulfo betaine; the chemical crosslinking agent is N,N-methylenebisacrylamide; and the photoinitiator is at least one of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 1-hydroxycyclohexylphenyl ketone, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
4. The method for preparing the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Preparing a Tempo-oxidized nanocellulose dispersion; (2) mixing N,N-carbonyldiimidazole and 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid, heating and stirring to obtain activated acidic imidazole lactone; adding 1 to 5 parts by weight of activated acidic imidazole lactone to 90 to 150 parts by weight of the Tempo oxidized nanocellulose dispersion obtained in step (1) under an inert gas atmosphere, reacting under heating and stirring conditions, and dialyzing in water after the reaction is completed to obtain a Tempo oxidized nanocellulose dispersion grafted with 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid; (3) Add 20 to 40 parts by mass of sodium acrylate and 10 to 30 parts by mass of zwitterionic sulfonate betaine to 150 to 200 parts by mass of the Tempo oxidized nanocellulose dispersion grafted with 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid obtained in step (2), add a chemical crosslinking agent and a photoinitiator under stirring, keep stirring to react, and after the reaction is completed, centrifuge to remove bubbles in the mixed dispersion to obtain the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink.
5. The preparation method according to claim 4, characterized in that: The solid content of the Tempo oxidized nanocellulose dispersion in step (1) is 2wt% to 5wt%.
6. The preparation method according to claim 4, characterized in that: The solid content of the Tempo-oxidized nanocellulose dispersion grafted with 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid in step (2) is 4wt% to 6wt%.
7. The preparation method according to claim 4, characterized in that: The molar ratio of N,N-carbonyldiimidazole to 4-cyano-4-[[(dodecylthio)thiomethyl]thio]pentanoic acid in step (2) is 0.5-2.
8. The preparation method according to claim 4, characterized in that: The reaction in step (2) is carried out at 30°C to 40°C with stirring for 3h to 6h, and the stirring speed is 500r / min to 1500r / min.
9. The preparation method according to claim 4, characterized in that: The reaction in step (3) is carried out at 50°C to 80°C with stirring for 24h to 48h, and the stirring speed is 500r / min to 1500r / min.
10. The use of the 3D printing nanocellulose / sodium acrylate / zwitterionic sulfonate betaine composite gel electrolyte ink according to any one of claims 1 to 3, characterized in that: The ink is used in the technical fields of supercapacitors, flexible wearable devices or lightweight electronic devices.